CHARACTERIZATION OF A AISI/SAE 4340 STEEL IN DIFFERENT MICROSTRUCTURAL CONDITIONS - Barros, Renato Araujo [UNESP]; Abdalla, Antonio Jorge; Rodrigues, Humberto Lopes; Pereira, Marcelo dos Santos [UNESP]; Hotza, D. (Trans Tech Publications Ltd, 2014)
The 4340 are classified as ultra-high strength steels used by the aviation industry and aerospace applications such as aircraft landing gear and several structural applications, usually in quenched and tempered condition. In this situation occurs reduction of toughness, which encourages the study of multiphasic and bainitic structures, in order to maintain strength without loss of toughness. In this study, ferritic-pearlitic structure was compared to bainitic and martensitic structure, identified by the reagents Nital, LePera and Sodium Metabisulfite. Sliding wear tests of the type pin-on-disk were realized and the results related to the microstructure of these materials and also to their hardnesses. It is noted that these different microstructures had very similar behavior, concluding that all three tested pairs can be used according to the request level.
Keywords: AISI/SAE 4340; microstructural characterization; sliding wear; pin-on-disk